Myths and beliefs about diabetic foot: A cultural study in outpatients with type 2 diabetes at the Hospital Regional de Lambayeque - Córdova López , Eglee Tais (2025)
Objective: To analyze and explore beliefs, myths, and fears about the care of diabetic foot (DF) in a hospital in northern Peru. Methods: A qualitative and analytic study was carried out using semi-structural interviews applied to patients recruited through a convenient sample limited by thematic saturation among individuals attending the Diabetic Foot Unit of Hospital Regional Lambayeque. The results were registered, transcribed, coded, and categorized manually with thematic analysis. Results: Ten individuals were interviewed. Three categories were obtained: a. myths and beliefs about the genesis of DF; unknown and spontaneous origin, the religion imposes the belief that DF are the results of divine punishment, magico-religious causes (witchcraft), or inadvertent lesions. B. myths and beliefs around management: avoid food that exacerbates DF, use of anti-inflammatory herbs, and request for a sorcerer consultation or auto prescription. C. living with fears and anxiety: amputation and limitations. Conclusion: Myths and beliefs were identified that need to be taken into account by healthcare professionals to improve the management of DF.